The linkage between the world oil price and Chinese energy-related stock price: Implications for risk management - Wen, Xiaoqian (Curtin University, 2015)
The asymmetric BEKK (Baba, Engle, Kraft and Kroner) econometric model and copulas are used to measure the linkage between the world oil price and Chinese energy stock price and discuss implications for risk management and energy policy. Asymmetric return and volatility spillovers are found between markets with new energy companies being more vulnerable than fossil fuel companies to the extreme changes in the world oil price. An optimally-weighted portfolio is the best risk management strategy.